Keeping Up with Telecom: Convergence, Broadband, and Access. - Bonnett, Tom (Public Management (00333611), 2002)
The Telecommunications Act of 1996 promised competition in local telephone markets and cable television services. This competition was expected to provide U.S. consumers with improved services and lower prices. Nonetheless, robust competition between entrenched, incumbent monopoly providers in cable TV and local telephone markets has remained an elusive target. Instead, there has been a wave of industry mergers and consolidations during the past six years. Advocates for competitive local exchange carriers regard this activity as an indication that the industry is headed toward the remonopolization of telecommunications. However, this judgment may be premature, as robust competition has continued in long-distance services and is now evident in such new services as data transport, Internet access, and wireless telephony.